COGNITIVE AND METACOGNITIVE SKILLS OF STUDENTS IN THE CONTEXT OF SMART-EDUCATION - E. V. Bataeva (Russian State Vocational Pedagogical University, 2019)
Introduction. Smart education, which has already become in many countries the standard of vocational training, is associated not only with the new technological format of education using Internet programs and smart gadgets, but also with the emergence of special styles and ways of carrying out educational activities. This entails the development of specific cognitive skills of students and methodological practices of teachers. At the same time, in modern theory of smart education, not enough attention is paid to the problem of formation of cognitive and metacognitive skills of students relevant to the format of smart learning. The aim of the research was to conduct a complex analysis of cognitive and metacognitive skills of students which are formed in the context of smart education; a critical analysis of modern concepts of cognitive and metacognitive development of students online.Methodology and research methods. The research methodology is based on competency-based, cognitive and system-activity approaches to the implementation of educational process. Scientific methods involve: analysis and synthesis of the content of sociological, socio-psychological, pedagogical and methodological literature.Results and scientific novelty. The methodological contradictions between the cognitive attitudes of smart education and the real cognitive and metacognitive competencies of students online are revealed. The focus of smart education on electronic learning formats poses risks of deformation of students' cognitive skills and narrowing the range of perception of information, which can be reduced by combining traditional education and e-learning in blended learning. Smart learning is aimed at the development of online trans-active memory, oriented towards the accumulation and passive use of ready-made electronic content. Cultivation of memory of this type is caused by supply of the ready electronic records of lectures and presentations, which students get without any effort and quite often remain not updated within pupils' / students' motivation deficiency, lack of the control and "live" pedagogical influence stimulating and coordinating thought processes. The orientation of smart-education on the transmission of information and mechnical reproduction can prevent the development of students' professional competencies, rather than on the formation of knowledge. The combination of online learning with practices of active listening and note-taking of auditory information (where there is a "face to face" communication with a teacher) can correct the deficiencies mentioned and contribute to the development of students' active memory, which can be initialized at any time. The critical view on metacognitive aspects of smart-education reveals its restrictions, which prevent proper acquisition of educational programmes in a similar format and which particularly express the underdevelopment of skills of students online, such as self-control and self-monitoring of the effectiveness of the learning process (as evidenced by the data of sociological and psychological research). In this regard, it is required to study and differentiate those concrete cognitive and metacognitive abilities, which can be acquired in the process of smarteducation, and those which are not developed in its borders. Additional verification has to be conducted in order to justify the assumption that educational activity in internet-space does not allow metacognitive skills to be developed and can be successful only through their preliminary formation in the conditions of students' and teachers' mutual cooperation. Practical significance. The research results and materials can be used in the preparation of educational methodological programmes aimed at the development of cognitive and metacognitive competencies of students online, as well as for correcting of the smart-education content.